2011
DOI: 10.1007/s10787-011-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Saraca asoca (Roxb.) Wilde on lysosomal enzymes and collagen metabolism in adjuvant induced arthritis

Abstract: Rheumatoid arthritis is a chronic, progressive and systemic inflammatory disorder mainly affecting the synovial joints. In the present study, we evaluated the anti-arthritic effect of the methanol extract of Saraca asoca (Roxb.) Wilde., (Fabaceae) on adjuvant induced arthritis by assessing paw swelling, body weight, the levels of lysosomal enzymes, protein bound carbohydrates, serum cytokines, urinary collagen and histopathology of joints. It was found that S. asoca methanol extract at doses of 50, 100 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This is the first time that an in vivo activity is being reported for compounds 6 and 8. The bark of S. asoca extract has earlier been studied for anti-inflammatory activity (Preethi & Krishnakumar 2011;Saravanan et al 2011) but the active compounds could not be identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first time that an in vivo activity is being reported for compounds 6 and 8. The bark of S. asoca extract has earlier been studied for anti-inflammatory activity (Preethi & Krishnakumar 2011;Saravanan et al 2011) but the active compounds could not be identified.…”
Section: Resultsmentioning
confidence: 99%
“…S. indica Linn., locally named as Ashoka, is prescribed by Ayurvedic physicians for various diseases, including, gynaecological disorders (Pradhan et al 2009;Misra 2013). It has been, recently, reported that the MeOH extract reduced paw swelling, increased body weight, reduced the level of lysosomal enzymes, decreased protein-bound carbohydrates, urinary collagen and serum cytokines as well as normalised the histopathology of joints (Saravanan et al 2011) and did not show any toxicity (Mukhopadhyay & Nath 2011). However, the anti-inflammatory compound could not be identified, so far.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The flowers also reported for medicinal property and used in diabetes, cancer and hemorrhagic dysentery. [234] Antimicrobial property of different plant parts including bark, flower and flower buds are reported in the literature. [5]…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of information on the analgesic effect of S. asoca in traditional medicine texts which has been demonstrated by experiments that used methanolic, petroleum ether, chloroform and aqueous extracts of the bark and leaves 33,42,56 . The analgesic property of S. indica has been attributed to its ability to inhibit sensory nerve stimulation (early phase), which was experimentally validated using three different methods, namely tail immersion method, tail flick method (which uses an analgesiometer) and formalin induced pain method 41,43 .…”
Section: Analgesicmentioning
confidence: 99%
“…The analgesic property of S. indica has been attributed to its ability to inhibit sensory nerve stimulation (early phase), which was experimentally validated using three different methods, namely tail immersion method, tail flick method (which uses an analgesiometer) and formalin induced pain method 41,43 . Since inflammatory responses contribute to the development of pain, the antiinflammatory activity described above might explain the analgesic effect of S. asoca during the late phase of pain development 11,33,42,70 . Thus, it is assumed that S. asoca extracts typically relieve pain by acting on both the central and peripheral nervous systems 56 .…”
Section: Analgesicmentioning
confidence: 99%